High-temperature Pumping of Silicon for Thermal Energy Grid Storage. (15th October 2021) - Amy, Caleb; Pishahang, Mehdi; Kelsall, Colin C.; LaPotin, Alina; Henry, Asegun
Abstract: As the cost of renewable energy falls below fossil fuels, the key barrier to widespread sustainable electricity has become availability on demand. Energy storage can enable dispatchable renewables, but only with drastic cost reductions compared to current batteries. One electricity storage concept that could enable these cost reductions stores electricity as sensible heat in an extremely hot liquid (>2000 °C) and uses multi-junction photovoltaics (MPV) as a heat engine to convert it back to electricity on demand, hours or days later. This paper follows previously reported technoeconomics and liquid containment, examining equipment that would be needed to exchange heat between resistive heaters, a molten silicon storage tank above 2000 °C, and a heat engine. Herein, we report on a pump that was designed and tested to circulate the liquid silicon between these three regions and the effect of spatial thermal cycling was simulated in models and experiments. While the pump successfully circulated silicon between 1800 and 2080 °C for 10 h, circulation with a temperature gradient caused it and other non-isothermal experiments to dissolve significantly due to the temperature dependent solubility of not only carbon, but also silicon carbide which otherwise protected the graphite infrastructure. Methods to reduce dissolution and an alternative embodiment are presented. Highlights: This study investigates pumping molten silicon for economical thermal storage of electricity. Pumping above 2000 °C using an all graphite infrastructure is possible and was thermally and mechanically successful. A compact, simple method successfully metered the pump flow rate above 2000 °C. The temperature dependent solubility of graphite and silicon carbide in silicon near 2000 °C caused dissolution. Alternative methods and materials are proposed to build on the overall pumping success for a system that could last decades.